Calculations of rate constants for reactions of first and second row cations - Gonzalez, A; Clary, D; Yanez, M (1997)
Calculations of rate constants for 35 reactions of first and second row monocations with different neutrals are presented. A combined rotationally adiabatic capture and centrifugal sudden approximation is used. The majority of predicted rate constants are in good agreement with the experimental measurements. An exploration of energetics of the potential energy surface for some of those cases in which prediction fails has been done using ab initio G2 theory. These cases usually correspond to situations in which the reaction is not as exothermic as the application of capture approximation requires or secondary barriers exist in the reaction path. Second row cations present these kind of problems due to their smaller electronegativity with respect to cations of the first row.